Thermographic study of the maxillofacial area: the possibilities and prospects in modern dentistry - Abdillah Imron NASUTION; Mikhail Nikolaevich PANKOV (Dentistry Faculty, 2022)
Thermal pattern of body especially skin can determine the changes in the human body and, the consequences it causes, and changes in normal temperature distribution are a sign of a pathological process. The objective of this essay is to review the possibilities and prospects of Infrared thermography in modern dentistry in order to support dental clinicians to develop and conduct an analysis of maxillofacial changes both the quantitative and quantitative depending on cold acclimation using infrared thermography. Literature were searched in all databases such as PubMed, Medline, and Google Search for articles published between 2019 and 2022. By means of a systematic online database search and based on the PRISMA guidelines related to word infrared thermography, dentistry, inflammation articles were identified using the search engines PubMed, Medline, and Google Scholar. After screening the abstracts and applying the eligibility criteria on those which were fully accessible, 165 articles were included in the review. Amount 145 studies were excluded due to the defined inclusion and exclusion criteria and 20 studies have finally been included in the evaluation process. This was followed by an analysis and discussion of the methodology KEYWORDS: Thermography, dentistry, maxillofacial area, Arctic Zone